Exploring the Potential of Whey Ultrafiltration Permeate in Wood Modification: Changes in Wood Hygroscopic and Thermal Behaviors - Assira Keralta; Jérémy Winninger; Julien Chamberland; Véronic Landry (BioResources)
Wood’s hygroscopic nature limits its outdoor applications. Technologies such as wood polyesterification, involving the in situ reaction of alcohols and carboxylic acids, densify the wood cell wall and potentially reduce hydroxyl group activity. Whey ultrafiltration permeate, a co-product of whey protein purification, which is rich in lactose, can be a source of OH groups for wood modification. This study explores lactose’s reactivity with biobased carboxylic acids and evaluates the resulting wood properties post-modification. Spectroscopic analyses confirmed that lactose reacts with carboxylic acids when heated above the melting point, and the Maillard reaction and caramelization may occur due to whey ultrafiltration permeate’s non-protein nitrogen substances and acidic medium combined with high temperatures. Fourier Transform infrared spectroscopy analysis verified that lactose and malic acid react within trembling aspen sawdust, significantly reducing moisture absorption and enhancing thermal stability. This study proposes a novel valorization of whey ultrafiltration permeate and a simple process for improving wood properties.